Exploring First-Time Mothers’ Experiences with the Mommy-Be App: A Qualitative Study on Breastfeeding Support and Technology Acceptance - Azniah Syam BScPH, MScPH, PhD; Indra Dewi MN, RN; Firawati Firawati MN, RN; Darwis Darwis RN, MSc, PhD; Imelda Iskandar MN, RN (Midwifery), PhD (SAGE Open Nursing, 2025)
Introduction Despite its numerous benefits, breastfeeding practices in Indonesia have faced several setbacks, especially after the pandemic, thus falling far short of the expected target. We need innovative technology-based solutions, like mobile health applications, to provide mothers with an alternative companion during nursing. This study aims to explore the experiences and feedback of first-time breastfeeding mothers using the Mommy-Be application. Method This study used a qualitative phenomenological approach involving six first-time breastfeeding mothers at a primary clinic in Makassar, Indonesia, from December 2023 to February 2024. We collected data through observation, structured in-depth interviews, and documentation. The Technology Acceptance Model (TAM) framework guided the thematic analysis of the data. Initial user responses indicated adaptive barriers that improved with the habit of accessing Mommy-Be . Mothers gave positive feedback on the visually appealing interface and found the application helpful in tracking breastfeeding routines and nutritional intake. The main challenges identified were internet connectivity issues and platform compatibility. Results The Mommy-Be application facilitates effective breastfeeding management and increases awareness of mental health and nutritional needs during breastfeeding. Positive feedback is consistent with previous studies emphasizing user-friendly interfaces and functionality. However, technical challenges highlighted the need for optimization for unstable network conditions and mobile platform compatibility. Conclusions This study received positive feedback for the Mommy-Be app, which aids in managing breastfeeding and monitoring nutrition. Future improvements should focus on network optimization and enhanced educational features. Ongoing training and support can further enhance user satisfaction and app acceptance.